Uterine rupture in the Netherlands: a nationwide population‐based cohort study - Zwart, JJ; Richters, JM; Öry, F; de Vries, JIP; Bloemenkamp, KWM; van Roosmalen, J (BJOG : an international journal of obstetrics and gynaecology, 2009)
Objective  To assess incidence of uterine rupture in scarred and unscarred uteri and its maternal and fetal complications in a nationwide design. Design  Population‐based cohort study. Setting  All 98 maternity units in the Netherlands. Population  All women delivering in the Netherlands between August 2004 and August 2006 (n = 371 021). Methods  Women with uterine rupture were prospectively collected using a web‐based notification system. Data from all pregnant women in the Netherlands during the study period were obtained from Dutch population‐based registers. Results were stratified by uterine scar. Main outcome measures  Population‐based incidences, severe maternal and neonatal morbidity and mortality, relative and absolute risk estimates. Results  There were 210 cases of uterine rupture (5.9 per 10 000 pregnancies). Of these women, 183 (87.1%) had a uterine scar, incidences being 5.1 and 0.8 per 10 000 in women with and without uterine scar. No maternal deaths and 18 cases of perinatal death (8.7%) occurred. The overall absolute risk of uterine rupture was 1 in 1709. In univariate analysis, women with a prior caesarean, epidural anaesthesia, induction of labour (irrespective of agents used), pre‐ or post‐term pregnancy, overweight, non‐Western ethnic background and advanced age had an elevated risk of uterine rupture. The overall relative risk of induction of labour was 3.6 (95% confidence interval 2.7–4.8). Conclusion  The population‐based incidence of uterine rupture in the Netherlands is comparable with other Western countries. Although much attention is paid to scar rupture associated with uterotonic agents, 13% of ruptures occurred in unscarred uteri and 72% occurred during spontaneous labour.